BACKONE equation of state for Cis-1, 3, 3, 3-tetrafluoropropene (R1234ze(Z)) - Huong, Phan Thi Thu; Anh, Lai Ngoc (Vietnam Journal of Mechanics, 2018)
This paper presents the study on the determination of the thermodynamic properties of Cis-1,3,3,3-tetrafluoropropene (R1234ze(Z)) with the BACKONE equation of state. The BACKONE's characteristic temperature T0, characteristic density ρ0, anisotropy factor α, and reduce quarupole moment Q*2 were found by fitting the BACKONE EOS to experimental data of vapor pressure and saturated liquid density. All thermodynamic properties such as vapor pressure, pressure in gaseous phase, saturated liquid density, and liquid density can be determined easily from the found molecular characteristic properties. Thermodynamic properties of the R1234ze(Z) were evaluated with available experimental data. Average absolute deviations between calculated vapor pressure data and experimental data were 0.43%. Average absolute deviations between calculated saturated liquid density data and experimental data were 0.43%. In the prediction of the thermodynamic properties, average absolute deviations between calculated liquid density data and experimental data were 0.68% and average absolute deviations between calculated gas density data and experimental data were 1.6%.